2013
DOI: 10.1042/bj20121454
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a pathway by which glucose regulates β-catenin signalling via the cAMP/protein kinase A pathway in β-cell models

Abstract: Pancreatic β-cells are highly responsive to changes in glucose, but the mechanisms involved are only partially understood. There is increasing evidence that the β-catenin signalling pathway plays an important role in regulating β-cell function, but the mechanisms regulating β-catenin signalling in these cells is not well understood. In the present study we show that β-catenin levels and downstream signalling are regulated by changes in glucose levels in INS-1E and β-TC6-F7 β-cell models. We found a glucose-dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 66 publications
2
33
1
Order By: Relevance
“…To provide support that NENS and Nic block the glucagon signalling pathway, we used CREB serine 133 as a readout, because this is a widely used measure of PKA activity202122. Control mice exposed to glucagon for 15 minutes on both the chow and high fat diets had a significant increase in serine 133 phosphorylation on CREB but both NENS and Nic blocked this effect (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…To provide support that NENS and Nic block the glucagon signalling pathway, we used CREB serine 133 as a readout, because this is a widely used measure of PKA activity202122. Control mice exposed to glucagon for 15 minutes on both the chow and high fat diets had a significant increase in serine 133 phosphorylation on CREB but both NENS and Nic blocked this effect (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Glucose can control β-catenin through a cAMP/PKA pathway 28 or by increasing β-catenin acylation and translocation to the nucleus 29 in other stem cell populations (Fig. 2).…”
Section: Intestinal Epithelial Cell Proliferation and Differentiationmentioning
confidence: 99%
“…In fact, before reaching the bloodstream and target organs such as the liver and pancreas, glucose is first absorbed and transport by enterocytes of the duodenum and jejunum. Along with its metabolic function, glucose by itself may act as a signaling molecule, not only in fission yeast such as Schizosaccharomyces pombe (Hoffman 2005) but also in mammals, as recently reported in INS-1E pancreatic ␤-cell lines (Cognard et al 2013). Although GLUT2 was proposed to have receptor-like function in ␤-cells and IECs (Leturque et al 2009), the exact cellular entity transmitting the glucose-stimulating effect is not clearly identified, and as such further study is required.…”
Section: Figmentioning
confidence: 92%
“…These results suggested that glucose could activate intracellular signaling pathway(s). In fact, it was previously proposed that changes in glucose levels regulate ␤-catenin signaling through a cAMP/PKA pathway (Cognard et al 2013). Herein, results show that an increase in glucose concentration from 1 to 25 mmol/L was sufficient to increase the luciferase activity associated with CREB promoter transactivation ( Fig.…”
Section: P2x7 Receptor Mrna Expression Is Increased Following Glucosementioning
confidence: 97%